PELATIHAN MOTIVASI BERAFILIASI MELALUI BIMBINGAN KELOMPOK DENGAN MENGGUNAKAN PERMAINAN PADA ANAK-ANAK PANTI ASUHAN KARUNA PUTRA - Eko Adi Putro; Ahmad Jawandi; Alfridus Naisoko (Lembaga Penelitian dan Pengabdian Masyarakat, 2021)
Affiliation motive is a need that every individual needs. Individuals need a need where one of these needs is the need to relate to other people or the need to make friends with others. There are symptoms of the Karuna Putra Orphanage children who have low affiliation motives, some children who form groups and between groups are not very close even though they are in one dormitory. There are also other groups who cannot accept the existence of other friends.. The implementation of this community service activity is by providing group guidance services. which in each meeting will discuss the topic of assignments with the theme of affiliation motivation and activities that include games, namely: a) word chain; b) Our Picture; c) Trip of Three Disabled Persons; d) Continue my story; e) Stand Together; f) positive thingking. The meaning of the game has to do with the themes that are presented